2011
DOI: 10.4113/jom.2011.1157
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphology of the Irish Rockall Trough, North Atlantic Ocean, mapped from multibeam bathymetric and backscatter Data

Abstract: Multibeam echosounder data collected by the Irish National Seabed Survey (INSS) between 2000 and 2001 in the Rockall Trough have been used by many projects to analyze the geomorphology and the sedimentary processes of the margins of the Trough. However, due to the low spatial resolution of 150-250 m and the amount of artefacts still embedded in the publicly available data, many geomorphological features have been overlooked. This paper shows that the same multibeam dataset can provide more detailed information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
(30 reference statements)
2
20
0
Order By: Relevance
“…for geomorphological mapping. Previous studies classifying morphology in either terrestrial or marine environments have been performed numerous times (Al-Hamdani et al, 2008;Cavalli and Marchi, 2008;Hogg et al, 2016;Höfle and Rutzinger, 2011;Ismail et al, 2015;Kaskela et al, 2012;Lecours et al, 2016;Sacchetti et al, 2011). These classification studies generally focus on either the marine or the terrestrial environment and do not cover the fine-scale morphology in the shallow water, due to the challenging environmental conditions.…”
mentioning
confidence: 99%
“…for geomorphological mapping. Previous studies classifying morphology in either terrestrial or marine environments have been performed numerous times (Al-Hamdani et al, 2008;Cavalli and Marchi, 2008;Hogg et al, 2016;Höfle and Rutzinger, 2011;Ismail et al, 2015;Kaskela et al, 2012;Lecours et al, 2016;Sacchetti et al, 2011). These classification studies generally focus on either the marine or the terrestrial environment and do not cover the fine-scale morphology in the shallow water, due to the challenging environmental conditions.…”
mentioning
confidence: 99%
“…Within the north-eastern Atlantic, iceberg scours have been previously recorded on the western Irish continental shelf and slope (Belderson et al, 1973;Benetti et al, 2010;Sacchetti et al, 2011;Ó Cofaigh et al, in press), on the Rockall Bank in UK waters (Kenyon et al, 2003), and on the Porcupine Bank where iceberg furrows, 50-500 m wide and hundreds of meters to over 20 km long, have been reported (O'Toole and Monteys, 2010). Between 2000 and 2004, the Irish portion of the Rockall Bank was fully surveyed using multibeam swath bathymetry under the auspices of the Irish National Seabed Survey (INSS) (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…It is characterised by water depths between 300 and 400 m and an approximate width of 100 km. To the north and to the west the Porcupine Bank displays a shelf break at c. 500 m water depth; the slope is steep and narrow towards the Rockall Trough (Sacchetti, Benetti, Georgiopoulou, Dunlop, & Quinn, 2011). To the south and southeast, the bank opens with a gentle slope to the deep embayment of the Porcupine Seabight.…”
Section: Geographical and Topographical Settingmentioning
confidence: 99%
“…These were recognised mainly on the northern edges of the study area at the top of the steep slopes running to the Rockall Trough (Sacchetti et al, 2011) and to the edge of the cluster of identified bedrock outcrops to the southeast of the bedrock plateau. Another two long escarpments (30 and 40 km long) were identified in the southern Porcupine Bank at 350-370 m water depth.…”
Section: Escarpmentsmentioning
confidence: 99%
See 1 more Smart Citation